(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: The study was aimed to evaluate the attributes related to hyperbilirubinaemia among neonates. Materials and methods: A total number of 120 neonates with hyperbilirubinemia included in the study. Data were collected using hospital records and by face-to-face interview of mother of those neonates using a predesigned questionnaire. Data were expressed as mean±SD and number (percent) as appropriate. Both descriptive and inferential statistics were considered in data analysis. Statistical analyses were performed using SPSS Software. Result: Of the total neonates, 57% were baby boys. In age group of 2nd to 7th days were 59.2% of neonates. According to the birth weight, neonates distribution was 38.3% in very low (<2000g), 42.5% low (2001-2500g) and 19.2% normal (>2500g) birth weight group. ABO incompatibility was found in 14.2% and Rh 8.3% cases of hyperbilirubinaemia. Birth trauma was found in 7.5% and congenital anomalies 3.3% neonates. Pre-maturity (gestational age <37 wks) was found in 73.3% cases. Normal vaginal delivery was performed in 59.2% of cases. Exclusive breast feeding was given by 43.33% mothers. Of the mothers 93.4% were housewives. Thirty percent (30%) of mothers were adolescents (<20 years) and 27.5% young adults (20 to 25 years). Of the 120 mothers 56.7% had primary level education. Low birth weight (<2000g to 2500g) neonates had significantly higher (p<0.005) serum bilirubin than the normal birth weight counterpart. Among the neonates of the mothers with GDM, 9.2% had serum bilirubin level above 20mg/dl and the distribution showed significant association (p<0.005). Conclusions: It is concluded that low birth weight and prematurity remained to the major causes of neonatal hyperbilirubinemia in neonates. Other common causes, particularly ABO and Rh incompatibility, are also present which could be avoided by meticulous clinical practice and burden of neonatal morbidity and mortality related to hyperbilirubinemia can be reduced. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17430 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 58-62